Tracking the Conservation Promise of Movement Ecology - Fraser, Kevin C.; Davies, Kimberley T. A.; Davy, Christina M.; Ford, Adam T.; Flockhart, D. T. Tyler; Martins, Eduardo G. (Frontiers in Ecology and Evolution, 2018)
From butterflies to elephants, the rapidly developing science of movement ecology is providing increasingly detailed spatio-temporal data on a wide array of mobile animals. Thus, this discipline also holds great promise for improving the conservation of wildlife. To measure progress towards this promise, we investigated the degree to which movement ecology research is connected to conservation goals as well as the proportion of studies that were incorporated into federal and international status assessments for mobile species at risk. We examined 13,349 “movement ecology” papers published between 1990 and 2014 and found that explicit connections to conservation and management were made in 35% (n = 4, 672) of these papers, with the number of connections increasing over time. We then measured the uptake of movement ecology research into species status assessment and recovery plans (n = 72 documents) produced by three different governance agencies for 12 endangered mobile species. We found that on average 60 % of available movement ecology research was used in the status assessment process, demonstrating that when movement ecology research is available, it is generally being utilized in conservation planning. However, for 25% of these species, there was little movement research available to be used, highlighting that knowledge gaps remain for some at-risk species despite the general growth of movement ecology research. We outline opportunities for movement ecology to promote more effective conservation of taxa that move.